2021
DOI: 10.3389/fphar.2021.640572
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Prevents Campylobacter jejuni-Induced Leaky gut by Restoring Occludin and Claudin-5 in the Paracellular Leak Pathway

Abstract: Campylobacter jejuni is a bacterial human pathogen causing gastroenteritis and sequelae like irritable bowel syndrome. Epidemiologists count the human campylobacteriosis by C. jejuni as the most common foodborne zoonosis and bacterial diarrheal disease worldwide. Based on bioinformatics predictions for potential protective compounds in campylobacteriosis, the question was raised whether the plant-based polyphenol resveratrol is sufficient to attenuate intestinal epithelial damage induced by C. jejuni. We inves… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…Nevertheless, administration of the pre-hormone VD protects against C. jejuni-induced epithelial barrier dysfunction in vitro and in vivo. VD should therefore be considered as a potentially useful therapeutic supplement, when combined with other barrier-protective, immunomodulatory, and anti-inflammatory compounds, such as curcumin or resveratrol [3,45,46], for prevention and treatment of acute and chronic gastrointestinal disorders.…”
Section: Jejuni Interference With the Vitamin D Pathwaymentioning
confidence: 99%
“…Nevertheless, administration of the pre-hormone VD protects against C. jejuni-induced epithelial barrier dysfunction in vitro and in vivo. VD should therefore be considered as a potentially useful therapeutic supplement, when combined with other barrier-protective, immunomodulatory, and anti-inflammatory compounds, such as curcumin or resveratrol [3,45,46], for prevention and treatment of acute and chronic gastrointestinal disorders.…”
Section: Jejuni Interference With the Vitamin D Pathwaymentioning
confidence: 99%
“…Some of these have also been shown to be effective in IBS. They did not show an anti-microbial effect, but rather an immunomodulatory and barrier-stabilizing effect, such as the polyphenols curcumin or resveratrol or the hormone vitamin D (calcitriol) [ 6 , 7 , 8 ]. In addition, vitamin D has been reported to protect against macromolecule influx into C. jejuni -infected intestinal epithelial cells and against bacterial translocation [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Natural compounds have been identified that may combat C. jejuni infection by enhancing barrier function and down-regulating immune activation, namely the polyphenols resveratrol and curcumin, and the pre-hormone vitamin D [ 6 , 7 , 8 ]. Complementary intervention strategies of this type are conceivable for acute infections, but could also be useful for oral use in the recovery phase of an infection or afterwards for the prevention of PI-IBS.…”
Section: Introductionmentioning
confidence: 99%
“…Tight junction proteins, ZO-1 and occludin, play an important role in maintaining the monolayer integrity of intestinal epithelial cells [ 54 ]. ZO-1 is a cytoplasmic plaque protein that connects transmembrane protein and cytoskeleton, while occludin can affect the tight junction of intestinal epithelial cells by regulating macromolecular flux, both of which are indicator of mucosal integrity, and decreased expression indicates impaired barrier integrity [ 55 , 56 ]. In our results, the expression of ZO-1 and occludin in the intestinal tract of NAFLD rats was significantly reduced but increased after SX intervention, suggesting that SX could repair the intestinal barrier by increasing the expression of ZO-1 and occludin, which was consistent with the above conclusion.…”
Section: Discussionmentioning
confidence: 99%